Rapid Manufacturing of Co-Cr-Mo Implants by Three-Dimentional Printing Process forOrthopedic Applications: Rapid manufacturing orthopedic implantsshrinkage - Dourandish, Mahdi; Simchia, Abdolreza; Godlinski, Dirk (Iranian Journal of Pharmaceutical Sciences, 2008)
The fabrication of complex-shaped parts out of (wt %) Co-28Cr-6Mo alloy bythree-dimensional printing (3DP) was studied using two grades of the alloy withaverage particle sizes of 20 and 75 μm. To produce sound specimens, 3DPprocessingparameters were tuned. The sintering behavior of the powders was characterized bythe dilatometric analysis. Batch sintering in argon atmosphere at 1280 °C for 2h wasalso performed. It was shown that complex-shaped biomedical parts with totalporosity of 12-25% and homogenous pore structure can be fabricated by the 3DPprocess.